Optimizing Students’ Higher Order Thinking Skill through Indonesian English Course Platform - Apriani, Eka; Muthmainnah, Muthmainnah; Marzuki, Abdul Gafur; Esmianti, Farida; Supardan, Dadan (Paedagogia: Jurnal Pendidikan, 2023)
As the compulsory subject at the senior high school, English is used for transferring and develop their knowledge, skill, and attitudes in the areas of science, technology, and art. English is crucial for the student in order to help them to understand the oral and written text in detail. Eventually, teachers have to prepare a good strategy to complete the student need of English in the class. Then, the school has HOTS as the strategy for the students. However, students are required to seek additional learning outside of school in order to enhance their learning in school. For this reason, Indonesian English course platform (Ruangguru) becomes the medium to optimize student’ HOTS. This quantitative research discussed 84 students of SMAN 1 Rejang Lebong. In obtaining the data, the eighty-four students of XII grade in academic year 2020/2021 were given a set of questionnaires to get the data whether Ruangguru can optimize students’ HOTS in learning English. The researcher collected the data, then determined the frequency and percentage of the students' responses. According to this study's findings, Indonesian English course platform (Ruangguru) can be a medium to optimize students’ HOTS beside learning English in the classroom. Based on three indicators that is provided by researcher, those are: Analyzing (71.83%), Evaluating (72.26%), and Creating (72.85%). Based on the result, Indonesian English course platform (Ruangguru) helps students to optimize students’ Higher Order Thinking in learning English